The role of the preacher monks for dissemination of Philosophy of Sufficiency Economy to people - ศิริบำรุงวงศ์, ภาณุกา (Chophayom Journal, 2019)
This research has an object to study the role of the monk preachers for dissemination Philosophy of sufficiency economy to people. The sample groups were 16 preacher monks that were registered to be preacher monks registration from four sectors of Thailand, four provinces, each province was chosen four monk preachers. The research tools were individual in-depth interview form, focus group discussion form and participation observation form. The research found that most of monk preachers didn’t take the philosophy of sufficiency economy to preach directly to the people because they still lacked the correct understanding of the philosophy of sufficiency economy but they preached the five precepts, principle of Dharma to connect with the concentration and intellect in order to make people conscious and live with enough life, reclusive and self-sufficient. At present, there are five preaching types such as single preaching (1 monk), interrogative-answer preaching (2-3 monks), sermon preaching, Dharma speeches and Dharma lectures. However, the preacher monks analyzed the situation and the listener to be opportuneness with place and time to choose which preaching type. For Styles and preaching techniques the preacher monks used easy listening technique, giving the examples techniques, a clear story techniques and there were some Dharma ideas in order to improve life and solve various problems. Keywords : Roles of the preacher monks, Philosophy of Sufficiency Economy, dissemination